2006
DOI: 10.1099/vir.0.81638-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new densovirus infecting the German cockroach, Blattella germanica

Abstract: A new DNA virus (Parvoviridae: Densovirinae, Densovirus) was isolated and purified from descendants of field-collected German cockroaches, Blattella germanica. Viral DNA and cockroach tissues infected with B. germanica densovirus (BgDNV) were examined by electron microscopy. Virus particles, about 20 nm in diameter, were observed both in the nucleus and in the cytoplasm of infected cells. Virus DNA proved to be a linear molecule of about 1?2 mm in length. BgDNV isolated from infected cockroaches infected succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…2H), in accordance with the bioinformatically predicted start point, provided that transcription is driven by the P1 promoter (37). Therefore, in contrast to NS transcripts, the 5Ј untranslated region for VP mRNAs is very short and comprises only 3 nt, exactly the same as for CpDNV (7).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…2H), in accordance with the bioinformatically predicted start point, provided that transcription is driven by the P1 promoter (37). Therefore, in contrast to NS transcripts, the 5Ј untranslated region for VP mRNAs is very short and comprises only 3 nt, exactly the same as for CpDNV (7).…”
Section: Resultsmentioning
confidence: 90%
“…3D, panel 2, lane 2. We cloned and sequenced all of the bands; subsequent analysis revealed that the largest two (approximately 2.2 and 2.4 kb, indicated by an arrow with a vertical line and a simple arrow, respectively) indeed corresponded to the full spliced and unspliced transcripts, respectively, with a transcription stop point at nt 2494, 19 nt downstream from the predicted polyadenylation signal (AAUAAA, nt 2513 to 2518) (37) (Fig. 2F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Pefudensovirus is represented by the DNV isolated from the cockroach Periplaneta fuliginosa. DNVs isolated from the cockroach Blatella germanica and the cricket Acheta domestica (3,13,23) have similar physicochemical properties since their genomes are also only 5.4 kb long, the sequences encoding their structural proteins are split in two ORFs in different frames, and their short (200 to 220 nt) telomeres fold into simple fold-back hairpins. However, their sequences are quite dissimilar.…”
mentioning
confidence: 99%